Penggunaan Media Peta Berbasis Google Earth Di MIN 2 Kota Kediri - Muhammad Ahmad Sukron; Moh. Turmudi (eL Bidayah: Journal of Islamic Elementary Education, 2019)
The importance of a technological approach to management is to be able to help the educational process that is in line with educational goals. By using learning media through google earth-based maps, able to overcome the problems faced by teachers in delivering material about social science subjects. The focus of this research is to describe the design of planning; implementation, and factors that support and hinder teachers in implementing learning. This research uses a qualitative approach and this research is descriptive in nature. In collecting data using methods of observation, interviews, questionnaires, and documentation. The results of this study include: first, determining the type of learning media, making learning plans, paying attention to the learning objectives in choosing media, recognizing the characteristics of students and learning media; second, techniques for managing interactive classes, steps for presenting teaching material, and responding to student characteristics; and third, supporting factors include: madrasas provide facilities, adequate teacher quality, student interest in instructional media, student motivation, student seriousness to pay attention to the material, and its effect on student learning outcomes. While the obstacle is inadequate infrastructure, and the expertise of teachers has less experience in operating Google Earth media.